Motivation, Engagement, and Work-Life Balance: Key Drivers of Employee Performance at An Indonesian Bank - Dewi Rogayah; Laura Lahindah (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study investigates the effects of work engagement, work motivation, and work-life balance on employee performance at Bank X. Utilizing Structural Equation Modeling (SEM) and Partial Least Squares (PLS), the research reveals that work motivation significantly and positively influences employee performance, indicating that higher motivation leads to better job performance. Conversely, while work engagement demonstrates a positive correlation with performance, its effect is statistically insignificant, suggesting that merely enhancing engagement is insufficient without supportive factors such as motivation and a conducive work environment. Additionally, work-life balance positively impacts performance, yet this is also not statistically significant, highlighting the need for improved implementation of work-life balance policies. Overall, the findings emphasize the interconnectedness of motivation, engagement, and work-life balance in enhancing employee productivity. The study provides actionable recommendations for Bank X, including the development of motivational programs, the implementation of flexible work policies, and the establishment of a positive organizational culture. By adopting these strategies, Bank X can foster a more productive and satisfying work environment, ultimately enhancing overall employee performance.